2017
DOI: 10.1016/j.jgr.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Improved antimicrobial effect of ginseng extract by heat transformation

Abstract: BackgroundThe incidence of halitosis has a prevalence of 22–50% throughout the world and is generally caused by anaerobic oral microorganisms, such as Fusobacterium nucleatum, Clostridium perfringens, and Porphyromonas gingivalis. Previous investigations on the structure-activity relationships of ginsenosides have led to contrasting results. Particularly, the antibacterial activity of less polar ginsenosides against halitosis-related bacteria has not been reported.MethodsCrude saponins extracted from the Panax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 34 publications
(37 reference statements)
0
49
0
2
Order By: Relevance
“…As Figure g shows, Qc loses one molecular glucose at the position of C‐3 and is converted to Qd, and then finally transformed to Qf. Unlike the thermal degradation of saponins in ginseng, polar ginsenosides could transform into less polar ginsenosides upon heating (Xue et al, ). Conversion of the quinoa saponin may be related to the enzymes present in bran, which is similar to the Oenning's study (Oenning, Juillerat, Fay, & Asp, ).…”
Section: Resultsmentioning
confidence: 99%
“…As Figure g shows, Qc loses one molecular glucose at the position of C‐3 and is converted to Qd, and then finally transformed to Qf. Unlike the thermal degradation of saponins in ginseng, polar ginsenosides could transform into less polar ginsenosides upon heating (Xue et al, ). Conversion of the quinoa saponin may be related to the enzymes present in bran, which is similar to the Oenning's study (Oenning, Juillerat, Fay, & Asp, ).…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of less polar ginsenoside was performed according to the previous report with slight modication. 29 NS was heated in an MLS-3750 autoclave (Sanyo, Osaka, Japan) at 130 C for 3 h to obtain heat-transformed saponins (HTS). HTS was loaded onto a LH-20 column and sequentially eluted with water and 95% methanol about three BV, respectively.…”
Section: Preparation Of Less Polar Ginsenosidesmentioning
confidence: 99%
“…The analysis of less polar ginsenoside was performed according to the previous report with slight modication. 29 Chromatographic analysis for the ginsenosides was performed using a SHIMADZU Prominence LC-20A HPLC instrument (Shimadzu Corporation, Kyoto, Japan) equipped with a YMC-Pack ODS-AM column (4.6 mm  250 mm, YMC Co., Ltd., Kyoto, Japan). The detection wavelength was set at 202 nm.…”
Section: Hplc Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…*** Significantly different from control group (p < 0.001). RGEF: hydrophobic fraction of RGE Also, based on the previous studies of the antimicrobial effect(Sung & Lee, 2008;Xue, Yao, Yang, Feng, & Ren, 2017) of red ginseng, saponins were identified as an effective ingredient having a pharmacological effect. However, this study demonstrated that red-ginsengderived polyacetylenes, in particular, panaxynol and panaxydol, have antimicrobial activities against P. acnes.…”
mentioning
confidence: 99%